Pressure sore incidence in the acute phase of rehabilittation [ie. rehabilitation] among patients with traumatic spinal cord injuries - Hlongwane, Nomacala Maria (Stellenbosch : Stellenbosch University, 2012)
Assignment (MPhil) -- University of Stellenbosch, 2006.